Impact of Digital Tools on Service Delivery Efficiency in Government Ministries, Anambra State (2015–2023) - Anaekwe, Victor Benjamine; Onuigbo , Ifeanyi Ositadinma; Okeke, Mary Ngozi (ASHA Publishing, 2025)
This study explored the impact of e-administration on service delivery efficiency in selected ministries in Anambra State amid rising demands for digital transformation in the public sector. Using a survey design, data were collected through structured questionnaires administered to staff across the ministries of Education, Finance, Works, and Women Affairs. The study combined primary data from respondents with secondary data from documents and literature and employed both descriptive and inferential statistical analyses. Results revealed mixed perceptions of digital progress, with many respondents expressing skepticism about the effectiveness and consistency of digital tool adoption. While some acknowledged gradual improvements, others highlighted persistent reliance on manual processes, uneven implementation across ministries, and challenges such as limited infrastructure, insufficient training, and inconsistent policy enforcement. Leadership support and infrastructure development were recognized as essential enablers, yet the overall effectiveness of training programs remained unclear. Furthermore, statistical analysis found no significant gender-based differences in perceptions of service delivery outcomes, suggesting that the impact of digitization is broadly experienced across demographic groups. Despite ongoing efforts, the study concluded that systemic obstacles continue to constrain the full benefits of digital governance in the state. It recommends greater investment in infrastructure, continuous staff development, and stronger policy enforcement to ensure that digital transformation leads to meaningful improvements in public service delivery.